Personal Security Checklist: A Comprehensive Approach to Digital Security - Hitesh Choudhary; Navish Ansari; Shraddha Shivaji Sandimani (ITEGAM-JETIA)
In today's hyper-connected society, protecting personal data is not only essential, but a continuous challenge. This article presents the design, development and evaluation of the “Personal Safety Verification List”, a comprehensive web -based platform that enables users to identify vulnerabilities in their digital lives and implement robust safety measures. The system categorizes tasks on three levels - essential, optional and advanced - areas such as authentication, safe navigation, messages, social media protection and safety of physical devices. Taking advantage of modern technologies such as React.JS, Next.JS, TypeScript and Chart.JS, the platform offers real -time progress tracking through dynamic views. Extensive tests and user's iterative feedback indicate that this integrated solution not only increases the awareness of cyber security, but also motivates proactive behavior, simplifying complex protection strategies.